Effect of feed energy levels on semen quality and freezability of young Murrah buffalo bulls - Kumar, Ajit; Singh, P.; Bhakat, M.; Singh, S.; Nitharwal, K.; Gupta, A.K. (Buffalo Bulletin, 2017)
Effect of feed energy levels on semen quality and freezability of Murrah buffalo young bulls was investigated. Eighteen bulls (age 24 mo and bwt 428 kg) were randomly allotted to three groups of six in each. Group 1 was kept as control and bulls in this group were fed as per NRC (2001) recommendations, while feed of Group 2 and Group 3 bullswas same as in control andadditional 10% and 20% higher energy was provided through molasses to bulls of Group 2 and Group 3, respectively. Monthly feedintake of every bull was recorded. Semen was collected using AV technique at weekly interval; reaction time of bulls was recorded at collection. Ejaculate volume (ml), mass motility (0 to 5 scale), individual sperm motility (%), sperm concentration (m/ml); percent viability, acrosome integrity and morphological abnormality in fresh semen and post thaw sperm motility, viability and acrosome integrity in frozen semen were evaluated with microscopic methods. Results showed that the DM intake was higher (P < 0.01) in Group 3 than Group 2 and control. Reaction time (second) was the lowest (P < 0.01) in Group 2 followed by Group 1 and Group 3. Sperm concentration (m/ml) and mass motility was found to be higher (P < 0.05) in Group 2 than Group 3 and control. Similar trend (P < 0.05) of percent sperm motility, viability and acrosome integrity amongthe groups was observed. Whereas, significantly (P < 0.05) higher percent sperm abnormality was obtained in Group 3 followed by Group 1 and Group 2. Post-thaw percent sperm motility, viability and acrosome integrity were significantly higher (P < 0.05) in Group 2 than control and Group 3. From this study it can be concluded that 10% higher energy provided to the bulls in Group 2 than the control improved quality significantly of fresh and frozen semenin comparison to the control and other treatment group.